Symbolic actions in times of crisis - Verdoy, SJ, Alfredo (Razón y fe, 2018)
A very few episodes, which can be seen as symbolic actions, have joined the high temperatures of the summer of 2012. On one hand these symbolic actions tell us about the depth of the social crisis we live in and on the other they show the possible ways ahead to avoid such actions being voiced again in the future. They also show the possible ways for Spanish people to stop blushing and surprising for the current status of the public affairs.
Keywords: crisis; symbolic actions; human being; Eurovegas; tupperware; 25S; Ecce Homo of Borja